TINJAUAN YURIDIS PENYELESAIAN HUTANG PIUTANG BERDASARKAN KETENTUAN PASAL 1820 KUHPERDATA - Johanudin Johanudin (Universitas 17 Agustus 1945 Samarinda, 2015)
ABSTRACTProvision of guarantees is significant in an agreement accounts payable. Debt underwriting problems can arise at any time and by anyone. In practice often found in addition to asking for collateral material creditor to the debtor, also ask for additional collateral in the form of a guarantee of non material or personal guarantee.This study aims to answer the formulation of the issues raised in this paper. The goal is to determine the legal consequences underwriting of debt between creditor with the insurer, and also to determine the legal consequences of debt underwriting between the insurer and the debtor with the insurer.In conducting this research the writer uses research methods normative juridical and sociological research methods. The author uses literature study based on books, literature, and legislation that have a relationship with problems in this study. I also conduct research directly to the field namely by interviewing the respondents related to the problems examined by using the question systematically arranged.The data obtained from this study are primary data and secondary data, then performed summarized data reduction by selecting the subject and prepared more systematically so easily directed. In this case the author uses descriptive analysis of normative, which is a method that aims to describe objectively in order to make repairs to the problems faced.The conclusion of this study can be seen how the legal relationship between the creditor and debt underwriting insurer, and how the legal relationship between the debtor and debt underwriting insurer and among the insurer. They will also be known to the rights and obligations of the parties involved in an agreement with the guarantee of individual accounts payable debt underwriting.Keywords : Debts and receivables, Article 1820 of the Civil Code.